2013
DOI: 10.1038/ncomms3837
|View full text |Cite
|
Sign up to set email alerts
|

Real-time influenza forecasts during the 2012–2013 season

Abstract: Recently, we developed a seasonal influenza prediction system that uses an advanced data assimilation technique and real-time estimates of influenza incidence to optimize and initialize a population-based mathematical model of influenza transmission dynamics. This system was used to generate and evaluate retrospective forecasts of influenza peak timing in New York City. Here we present weekly forecasts of seasonal influenza developed and run in real time for 108 cities in the USA during the recent 2012-2013 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
340
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 276 publications
(348 citation statements)
references
References 20 publications
7
340
0
1
Order By: Relevance
“…Shaman et al 4, 5. used an ensemble adjustment Kalman filter (EAKF) and an SIRS infection model to predict seasonal influenza outbreaks in 108 cities across the USA and showed that outbreak peak timing could be predicted 4–6 weeks in advance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shaman et al 4, 5. used an ensemble adjustment Kalman filter (EAKF) and an SIRS infection model to predict seasonal influenza outbreaks in 108 cities across the USA and showed that outbreak peak timing could be predicted 4–6 weeks in advance.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of recursive Bayesian estimation methods (‘filters’) have been used for such forecasting purposes,1, 2 often in combination with Internet search query surveillance data and mechanistic models of infection 3, 4, 5, 6, 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have used a single data source [1,19,20] or a primary data source that was modulated by a secondary data source ('ILI+') [21,22]; in both cases single datasets were used to generate and evaluate the forecasts.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…This time lag is far from optimal for decision-making purposes. To alleviate this information gap, multiple methods combining climate, demographic, and epidemiological data with mathematical models have been proposed for real-time estimation of flu activity (18,(21)(22)(23)(24)(25). In recent years, methods that harness Internet-based information have also been proposed, such as Google (1), Yahoo (2), and Baidu (3) Internet searches, Twitter posts (4), Wikipedia article views (5), clinicians' queries (6), and crowdsourced selfreporting mobile apps such as Influenzanet (Europe) (26), Flutracking (Australia) (27), and Flu Near You (United States) (28).…”
mentioning
confidence: 99%